Alterations in protein glycosylation in PMA-differentiated U-937 cells exposed to mineral particles. - Trabelsi, N (1997)
Carbohydrate moieties of cell glycoconjugates play a pivotal role in molecular recognition phenomena involved in the regulation of most biological systems and the changes observed in cell surface carbohydrates during cell activation or differentiation frequently modulate certain cell functions. Consequently, some aspects of macrophage response to particle exposure might conceivably result from alterations in glycosylation. Therefore, the effect of mineral particles on protein glycosylation was investigated in phorbol myristate acetate (PMA)-differentiated U-937. Jacalin, a lectin specific for O-glycosylated structures, showed a global increase in O-glycosylation in particle-treated cells. In contrast, no significant modifications were observed with concanavalin A, a lectin that recognizes certain N-glycosylated structures. The sialic acid-specific lectins Sambucus nigra agglutinin and Maackia amurensis agglutinin and the galactose-specific lectin Ricinus communis agglutinin revealed a complex pattern of alterations in glycoprotein glycosylation after crystalline silica or manganese dioxide treatments. Expression of sialyl Lewis(x), a glycosylated structure implicated in leukocyte trafficking, could not be detected in control or treated cells. This finding was consistent with the decrease in sialyl Lewis(x) expression observed during PMA-induced differentiation. In conclusion, various treatments used in this study induced quantitative as well as qualitative changes in protein glycosylation. Whether these changes are due to glycosidase release or to an alteration in glycosyltransferase expression remains to be determined. The potential functional implications of these changes are currently under investigation.